STRENGTHENING OF PLAIN CEMENT CONCRETE BEAM USING FIBER REINFORCED POLYMER COMPOSITES (International Journal of Food and Nutritional Sciences, 2021)
A great deal of investigation is now being directed around the globe into the utilisation offibre reinforced polymer wraps, coverings, and sheets in the upkeep and fortification of built up huge people.Fiber-reinforced polymer (FRP) treatment has shown to be a very effective method of repairing and reinforcingbuildings that have become mainly weak over time. In comparison to traditional repair systems and conventionalmaterials, FRP repair systems provide a financially viable alternative